Antimicrobial Therapy and Antimicrobial Stewardship in Urosepsis - Tae Hoon Oh (Urogenital Tract Infection)
Since the latest knowledge on the treatment and countermeasures for sepsis is being updated at a rapid pace, becoming familiar with the Surviving Sepsis guidelines is helpful for patient prognosis. Extended-spectrum beta-lactamases (ESBL) are important factors when selecting early empirical antibiotics for sepsis caused by urinary tract infections. For severe septic shock, prolonged infusion and combination therapy need to be considered.